INTERPRETATION OF JUSTICE IN THE MEMORABLE STORY OF GHAFUR GHULAM - Bozarova Elmira (Web of Journals Publishing, 2025)
This article analyzes the fate of a person described in the story “The Stranger” by Ghafur Ghulam, the issues of ensuring justice and the analysis of the images in the work, and the strength of the Ghafur Ghulam fist.
Keywords: Ghafur Ghulam, Qissa, Memoriam, gender equality, human interpretation, social equality, mentality.